2019
DOI: 10.1016/j.heliyon.2019.e01732
|View full text |Cite
|
Sign up to set email alerts
|

An emerging new fowl adenovirus genotype

Abstract: In this work, we examined the diversity of fowl adenovirus (FAdV) types occurring in Hungary. From diseased chicken flocks in Eastern Hungary, 29 FAdV strains were isolated between 2011 and 2015. We performed molecular typing of the isolates based on their partial hexon sequences. The results showed that representatives from every FAdV species from A to E are present in Hungary, but compared to the findings from our previous survey, a lower number of different FAdV types were detected. Inclusion body hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The most notable divergence between FAdV-3 and other type members existed in ORF19. Similar to a recent finding in FAdV-B [69], this gene (and its predicted protein) was as divergent within the species as from its closest relative of another species, possibly suggesting that it had been derived in independent events from a reservoir outside the species.…”
Section: Discussionsupporting
confidence: 80%
“…The most notable divergence between FAdV-3 and other type members existed in ORF19. Similar to a recent finding in FAdV-B [69], this gene (and its predicted protein) was as divergent within the species as from its closest relative of another species, possibly suggesting that it had been derived in independent events from a reservoir outside the species.…”
Section: Discussionsupporting
confidence: 80%
“…FAdV‐1 has been reported several times from birds other than chickens, including quail and Alagoas curassow, a pheasant‐like bird, the wild populations of which became extinct. Nowadays, novel FAdV types are reported exceptionally rarely; however, several strains showing significant divergence from FAdV‐5 were just described in Central Europe as candidate type FAdV‐13 . During metagenomics studies on fecal samples from Australian wild birds, partial sequences of an aviadenovirus were identified in Pacific black duck .…”
Section: Advs In Birds (Aviadenovirus Atadenovirus Siadenovirus)mentioning
confidence: 99%
“…The wild oyster populations of the Atlantic are likely to be reservoirs of viruses with a higher genetic diversity than the cultured populations of the Thau lagoon, as indicated by previous studies showing a lower viral diversity in hatchery−reared oysters relative to wild individuals ( Vendrami et al, 2019 ). In full support of these observations, a higher host genetic diversity is expected to generate a higher viral diversity since viruses are obligatory cellular parasites, which implies that the virus and the host partners reciprocally affect each other’s evolution ( Kajan et al, 2019 ). Regardless of the origin of this diversity, our analysis revealed that the OsHV-1 μVar diversity along French coasts is higher than previously described ( Burioli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 94%